Environmental separation and enrichment of gold and palladium ions by amino-modified three-dimensional graphene. Issue 5 (21st January 2019) - Li, Jing; Wang, Shaoxia; Wang, Feng; Wu, Xuran; Zhuang, Xuming
Abstract : The excellent adsorption properties of three-dimensional graphene (3DG) can be further enhanced by triethylenetetramine modification to increase its adsorption capacity for precious metal ions. Abstract : The excellent adsorption properties of three-dimensional graphene (3DG) can be further enhanced by triethylenetetramine modification to increase its adsorption capacity for precious metal ions. Herein, we successfully synthesized an amino-modified 3DG (N-3DG) adsorbent with improved adsorption conditions with regards to pH value, dosage, and adsorption time. Adsorption equilibrium was reached at pH 3 over 120 min. In addition, the theoretical basis for the adsorption of N-3DG is provided by fitting the adsorption isotherm model. The synthesized material was tested in seawater and lake water samples for the adsorption of precious metals, namely Au(iii ) and Pd(ii ), achieving a recovery rate of 87% to 106% as assessed by inductively coupled plasma mass spectrometry. Thus, N-3DG showed good adsorptivity. The present results indicate that N-3DG materials could have a viable application in environmental and sewage treatment in the near future.